Pengaruh Partisipasi Penyusunan Anggaran terhadap Kinerja Aparat Pemerintah Daerah Dengan Budaya Organisasi, Komitmen Organisasi, Motivasi, Desentralisasi, dan Job Relevant Information Sebagai Variabel Moderasi - Nazaruddin, Ietje; Setyawan, Henry (Journal of Accounting and Investment, 2011)
This research was conducted to examined the influence of budgetary Participation to the performance of local government apparatus with organizational culture, organizational commitment, motivation, desentralization, and job relevant information as a moderating variable. The samples in this study using purposive sampling that is non probability sample that conform with certain criteria or considerations. The sample in this study are structural officials in the District Government of Kulon Progo which amounted to 104 respondents. The results of this study indicate that budgetary participation is not influence positive on the performance of local government apparatus. Organizational culture as a moderating role in the relationship between budgetary participation on the performance of local government apparatus. Organizational commitment, motivation, decentralization, and job relevant information can’t moderate the relationship between the budgetary participation with the performance of local government apparatus.